Identification of equine herpes virus 5 in horses with lymphoma - Vander Werf, Karie A.; Davis, Elizabeth G.; Janardhan, Kyathanahalli; Bawa, Bhupinder; Bolin, Steve; Almes, Kelli M. (My University, 2014)
Equine multinodular pulmonary fibrosis, equine herpesvirus 5 (EHV-5), and multicentric lymphoma were discovered in one patient. Review of gamma herpesvirus activity in humans revealed a propensity for lymphoproliferative disorders associated with infection. The objective was to determine the frequency of EHV-5 in lymphoma tissues and compare with the frequency found in the lymph nodes of clinically normal horses. Case control investigation of lymphoma-positive tissues and analysis via polymerase chain reaction (PCR) for EHV-5 was performed on 12 horses. Prospective collection and PCR analysis of lymph nodes (mesenteric or submandibular) for EHV-5 was performed on 21 control horses. Thirteen samples of lymphoma-positive tissues and fluid were submitted for PCR analysis for EHV-5. Of these, 67% was positive. In the control horse population, 14% was positive for EHV-5 (P = .004). Neoplastic samples positive for EHV-5 were classified as T-cell rich B-cell lymphoma (three), T-cell lymphoma (one), one was nondifferentiated, and two were not stained. Gamma herpesviruses in humans have been associated with lymphoproliferative diseases such as Kaposi sarcoma and Burkitt lymphoma. This study reveals an increased frequency of EHV-5 (gamma herpesvirus) in horses diagnosed with lymphoma compared with healthy control horses. Although the exact role this virus plays in the initiation or perpetuation of lymphoproliferative neoplasia is unknown, EHV-5 may be an etiologic agent associated with the development of some types of equine lymphoma.
Keywords: Equine multinodular pulmonary fibrosis; Equine herpes virus 5; Multicentric lymphoma; Equine lymphoma